Mutual interactions between objects oscillating in isotopically pure superfluid 4He in the T → 0 limit - Garg, D.; Efimov, V.B.; Giltrow, M.; McClintock, P.V.E.; Skrbek, L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We report the results of experiments to explore interactions between physically separated oscillating objects in isotopically pure superfluid 4He at T ~ 10 mK. The investigations focused mainly on 32 kHz quartz tuning forks, but also consider a nearby 1 kHz oscillating grid. The low-drive linewidth (LDL) and resonant frequency fd of a detector fork were monitored while the maximum velocity of a transmitter fork, separated from the detector by a few mm, was varied over a wide range. Clear evidence was found for mutual interactions between the two forks, and for the influence of the grid on the forks. Monitoring the detector's LDL and fd provides evidence for a generator critical velocity in the range 0.3 < vc1 <1.0 cm/s for onset of the detector responses, in addition to a second critical velocity vc2 ~ 13 cm/s probably corresponding to the production of quantum turbulence at thegenerator. The results are discussed, but are not yet fully understood.